HUBUNGAN RIWAYAT KELUARGA DAN PENGGUNAAN KONTRASEPSI HORMONAL PADA KEJADIAN KANKER PAYUDARA WANITA USIA PRODUKTIF DI RS GRHA PERMATA IBU DEPOK TAHUN 2022 - Muhammad Kevin Auliansyah Akbar (2023)
Breast cancer has an ever-increasing prevalence and is the second leading cancer related deaths in Indonesia. Risk factors for breast cancer are family history, use of hormonal contraception, age, lifestyle, radiation and exposure to carcinogens. This study aims to determine the relationship between family history and the use of hormonal contraception on the incidence of breast cancer. Methods: The study used an observational analytic method with a cross sectional approach. The research sample was women of reproductive age diagnosed with breast cancer who visited Grha Permata Ibu Depok Hospital, totaling 34 patient using a total sampling technique. Medical record research data. Results: Samples were diagnosed with No Special Type (NST) breast cancer (47.1%), Invasive Lobular (17.6%), and Ductal Carcinoma In Situ (DCIS) (35.3%). Family history was 58.8% and history of contraceptive use over 4 years was 52.9%. Fisher exact test results obtained [p = 0.017] with an OR value of 6.81, which found a relationship between family history and the incidence of breast cancer, and [p = 0.492] with an OR value of 0.495, which found no relationship between the use of hormonal contraception on the incidence of breast cancer. Society needs to increase awareness and early detection of breast cancer, especially for those who have higher risk factors, namely family history.